If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -2 = 2(5 + -7) Reorder the terms: -2 + y = 2(5 + -7) Combine like terms: 5 + -7 = -2 -2 + y = 2(-2) Multiply 2 * -2 -2 + y = -4 Solving -2 + y = -4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = -4 + 2 Combine like terms: -2 + 2 = 0 0 + y = -4 + 2 y = -4 + 2 Combine like terms: -4 + 2 = -2 y = -2 Simplifying y = -2
| 2m-4=2m | | y^2-14y+6=0 | | 6(5-3u)=-4u-17 | | 9x+-15=10x | | 24-8=-2-10 | | 5x^2+2x=-4 | | 0=(13-0.25x)(12+4x) | | 4x-12+3x=50 | | x^2+2x-4=3x-8 | | 84=4(3m+3) | | (h+12)(h-3)(h)=324 | | 2(3x-6)-3=2(x-5)+11 | | 0.73v+37.9=16v | | -x-3=2x+3 | | 0.75x-4=-10 | | h+10.6=-10.6 | | -1.5(4-n)+2.8=n | | 5x+x=x | | 16+(f+4)= | | x-54=102 | | 3x+18=4x-26 | | 8(c+10)=6(c+4) | | 4x-y=2-2y | | 4x-22=x+5 | | 3x=15/3 | | 21-4x=3(7-8x) | | 2(2+6x)=40 | | 11b-8=-b-12 | | 3w+10=272 | | 1-5x(9k)^(5/3)=-1214 | | -7g+9=-8g+4g | | 40+5x+4y=180 |